The role of ubiquitination and deubiquitination in the pathogenesis of non-alcoholic fatty liver disease - Zhang, Lihui; Liu, Sutong; Zhao, Qing; Liu, Xiaoyan; Zhang, Qiang; Liu, Minghao; Zhao, Wenxiao (Frontiers in Immunology, 2025)
Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases and is closely associated with metabolic abnormalities. The causes of NAFLD are exceedingly complicated, and it is known that a variety of signaling pathways, endoplasmic reticulum stress, and mitochondrial dysfunction play a role in the pathogenesis of NAFLD. Recent studies have shown that ubiquitination and deubiquitination are involved in the regulation of the NAFLD pathophysiology. Protein ubiquitination is a dynamic and diverse post-translational alteration that affects various cellular biological processes. Numerous disorders, including NAFLD, exhibit imbalances in ubiquitination and deubiquitination. To highlight the significance of this post-translational modification in the pathogenesis of NAFLD and to aid in the development of new therapeutic approaches for the disease, we will discuss the role of enzymes involved in the processes of ubiquitination and deubiquitination, specifically E3 ubiquitin ligases and deubiquitinating enzymes that are important in the regulation of NAFLD.